ANALISIS YURIDIS TERHADAP EKSEKUSI HAK TANGGUNGAN (STUDI KASUS PUTUSAN PERKARA PERDATA NOMOR 38/PDT.G/2012/PN.PBR) - Simamora, Try Jaya; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Land as collateral is a good guarantee property because it has economic value, therefore the author is interested in the title